SWOT ANALYSIS AS A TOOL OF STRATEGIC MANAGEMENT OF THE HEMP INDUSTRY - LYSHENKO, Margarita (Herald of Khmelnytskyi National University. Economic sciences, 2022)
During the last decade, the hemp industry has undergone significant changes, which was caused by the lifting of restrictions on the cultivation of hemp, but it has not achieved significant success. Producers of hemp products are forced to constantly adapt to constant changes in the external environment. The number of countries developing the hemp industry is growing every year, and competition is intensifying. The high level of state regulation of the industry does not cause producers to want to grow this crop. The COVID-19 pandemic and the declaration of martial law in Ukraine significantly reduce the access of producers to foreign markets and curtail state funding programs for the hemp industry. The purpose of the study is the analysis and proposals for the application of the SWOT-analysis matrix by enterprises for the cultivation and processing of industrial hemp products for the formation of a complex of anti-crisis strategies. It is proved by examples that the only measure of the strength of one or another factor is a comparison of them with competitors. On the basis of the given SWOT matrix, a critical analysis of some factors of strengths and weaknesses, opportunities and threats was carried out. Four questions with examples of answers have been created, which must be answered by enterprises on the basis of the compiled matrix. The main stages of conducting a SWOT analysis are outlined, among which the stages of "turning inside out" and filling the intersection cells with certain actions deserve special attention, which provides enterprises with a large number of different variations for making management decisions. It is proposed to supplement the categories of "strong" and "weak" sides with the concept of "basic" conditions. Attention is focused on the mistakes that enterprises make during the compilation of the SWOT analysis matrix.